The Impact of Corporate Governance, Technology-Based Risk Management, and Reporting Transparency on Investor Confidence in Indonesia's Technology Industry - Lena Erdawati; Ahmad Eko Saputro; Yanti Arnilis; Sri Juminawati; Eko Sudarmanto (Westscience Press, 2026)
This study investigates the impact of corporate governance, technology-based risk management, and reporting transparency on investor confidence in the Indonesian technology industry. Employing a quantitative research design, data were collected from 135 respondents with experience and knowledge related to investment and technology-based firms in Indonesia using a structured questionnaire measured on a Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to examine the relationships among the proposed constructs. The results reveal that corporate governance has a positive and significant effect on investor confidence, indicating that effective governance mechanisms enhance trust and reduce perceived agency problems. Technology-based risk management is also found to positively influence investor confidence, suggesting that the adoption of digital tools and systems for risk identification and mitigation signals organizational resilience and preparedness. Furthermore, reporting transparency demonstrates the strongest positive effect on investor confidence, emphasizing the critical role of clear, accurate, and timely disclosure in reducing information asymmetry. Collectively, the findings suggest that strengthening governance practices, leveraging technology in risk management, and improving reporting transparency are essential strategies for enhancing investor confidence and supporting sustainable growth in Indonesia’s technology sector. This study contributes to the literature on corporate governance and investment behavior in emerging markets and offers practical insights for managers, regulators, and investors.